2005
DOI: 10.1097/01.wnp.0000151146.91147.a1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Electromyography in Children and Adolescents

Abstract: The diagnostic accuracy in pediatric neurology has been considerably improved by new methods such as magnetic resonance imaging and molecular genetic analysis. However, standard diagnostic techniques continue to play an important role. The authors analyzed the diagnostic value of electromyography (EMG) and nerve conduction studies (NCS) in a retrospective study of 498 pediatric patients. The overall consistency between EMG results and the final clinical diagnosis in all children examined was 98%. In myogenic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
25
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 15 publications
12
25
0
Order By: Relevance
“…In a study of 498 children, 17% of the EMG investigations were hampered by lack of cooperation because of fear or pain. 43 The sensitivity of EMG in detecting neurogenic disorders was very high in every age group (88%-100%). 12,19,43 EMG has more problems in detecting myopathies, especially in children.…”
Section: Muscle Ultrasound Compared To Other Diagnostic Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 498 children, 17% of the EMG investigations were hampered by lack of cooperation because of fear or pain. 43 The sensitivity of EMG in detecting neurogenic disorders was very high in every age group (88%-100%). 12,19,43 EMG has more problems in detecting myopathies, especially in children.…”
Section: Muscle Ultrasound Compared To Other Diagnostic Techniquesmentioning
confidence: 99%
“…12,19,43,81 As EMG is a measurement of function, and ultrasound is concerned with structure, the use of both techniques is complementary for the most part. Application of dynamic muscle ultrasound can provide a bridge between the study of muscle structure and function.…”
Section: Figure 11mentioning
confidence: 99%
See 1 more Smart Citation
“…As well, EMG had more difficulty in detecting myopathies in young children; the sensitivity increased from 25% in infants to 91% in children above 5 years of age. 18 Alternatively, MRI can visualize deeper muscles and detect changes that are indicative of disease progression in neuromuscular diseases; however, as mentioned above, MRI has a number of potential limitations, especially in the pediatric population. Furthermore, Zaidman et al 19 found that nerve ultrasound was more sensitive than MRI in detecting focal neuropathies or brachial plexopathy.…”
Section: Practical Uses Of Muscle Ultrasound As a Screening Tool For mentioning
confidence: 99%
“…Earlier studies have addressed the diagnostic value of pediatric EMG for a broad range of disorders involving the peripheral nervous system, particularly as it compares with the final diagnoses reached through an integration of clinical, laboratory, histological, radiological, and genetic data . The general consensus from these investigations is that EMG remains an important diagnostic tool in children, with a high detection rate for neurogenic and neuromuscular junction pathology, and less consistent sensitivities for myopathic patterns at young ages (<2 years) …”
mentioning
confidence: 99%